US FOREIGN SERVICE INSTITUTE: HISTORICAL RETROSPECTIVE - Tetiana KLYNINA (Актуальні питання суспільних наук та історії медицини, 2020)
Purpose of the study. The article analyzes the history of the formation of a scientific center at the US